A mitochondria-localized iridium(iii)–chlorin E6 conjugate for synergistic sonodynamic and two-photon photodynamic therapy against melanoma. Issue 12 (16th May 2022) - Chen, Zhuoli; Feng, Tao; Shen, Jinchao; Karges, Johannes; Jin, Chengzhi; Zhao, Yukun; Ji, Liangnian; Chao, Hui
Abstract : A mitochondria-localized iridium(iii )–chlorin e6 conjugate was developed for synergistic sonodynamic and two-photon photodynamic therapy against melanoma A375 cells and A375 mice xenografts. Abstract : While melanoma in its early stages can be successfully treated, the prognosis strongly worsens with increasing depth of tumors. Capitalizing on this, there is an urgent need for the development of novel strategies and therapeutic compounds that are able to efficiently and selectively treat deep-invasive tumors. To overcome this limitation, herein, the covalent conjugation of chlorin e6 with a cyclometalated iridium(iii ) complex into a novel conjugate that is able to localize in the mitochondria and excited by ultrasound radiation and two-photon light irradiation for deep-invasive tumors by combined sonodynamic and photodynamic therapy is presented. To ensure selective treatment of the cancerous tissue, the conjugate was encapsulated with an amphiphilic biotin functionalized polymeric carrier into cancer-targeting nanoparticles. Based on the synergistic therapeutic properties of ultrasound radiation and light irradiation, the encapsulated conjugate was found to have a cytotoxic effect on human melanoma cells in the nanomolar range. While selectively accumulating in tumorous tissues, the encapsulated conjugate was found to have a distinguished therapeutic effect on melanoma tumors inside a mouse model upon exposure to deeply penetrating ultrasound radiation and light irradiation within a single treatment.